The Effects of eGFR Change on CVD, Renal, and Mortality Outcomes in a Hypertensive Cohort Treated With 3 Different Antihypertensive Medications. (19th January 2018) - Barzilay, Joshua I; Davis, Barry R; Pressel, Sara L; Ghosh, Alokananda; Rahman, Mahboob; Einhorn, Paula T; Cushman, William C; Whelton, Paul K; Wright, Jackson T
Abstract: BACKGROUND: Impaired renal function is a risk factor for cardiovascular disease, end-stage renal disease (ESRD), and mortality. The impact of short-term renal function decline on outcomes is less well studied. The association of antihypertensive medications with the impact of short-term estimated glomerular filtration rate (eGFR) decline is not known. METHODS: We examined 20, 207 hypertensive participants with baseline and 2-year creatinine levels from which eGFR changes were estimated. The associations between eGFR change with incident coronary heart disease (CHD), stroke, heart failure (HF), all-cause mortality, and ESRD during 2.9 years of in-trial follow up, and with mortality during in-trial and post-trial follow-up (7.6 years), were studied. Results were assessed by primary hypertension (HTN) treatment (chlorthalidone, lisinopril, and amlodipine) and adjusted for baseline eGFR levels. RESULTS: In the short run, an eGFR decline below the cohort median (−1.28 ml/minute/1.73 m 2 /2 years) vs. above the median, or a 5 ml/min/1.73 m 2 /year decline vs. no decline, was associated with significant hazard risk for CHD (1.06–1.28), HF (1.24–1.91), ESRD (2.84–6.01), and mortality (1.08–1.19), but not with stroke risk. In the long term, there was a significant association with mortality (1.11–1.34). Interaction terms for outcomes by antihypertensive treatments were not statistically significant except for ESRD between amlodipine vs. chlorthalidone (hazard ratio: 3.17 [2.59, 3.88] vs. 2.41 [1.98, 2.97]; P interaction = 0.005) for a 5 ml/min/1.73 m 2 /year eGFR decline. CONCLUSION: Decline in eGFR over 2 years is associated with increased risk of clinical outcomes beyond the effects of baseline eGFR. These risks were the same irrespective of the primary medication used to treat HTN.